Проектно-конструкторские компетенции бакалавров: теория и практика - Вехтер Е. В. Евгения Викторовна; Захарова А. А. Алена Александровна; Минин М. Г. Михаил Григорьевич; Сафьянников И. А. Игорь Александрович (Томск, Изд-во ТПУ, 2013)
В фонде НТБ ТПУ отсутствует